(untitled) (AIUB Journal of Science and Engineering (AJSE), 2024)
This study investigated the steam power plant performances using a response surface methodology (RSM). The thermodynamic simulations are conducted by the Engineering Equation Solver (EES) program for distinct parameters such as inlet temperature (350≤T3≤600°C), boiler pressure (5000≤P3≤15000kPa), and condenser pressure (5≤T1≤15 kPa). A centered composite design (CCD) with process parameters was used for statistical analysis. A second-order regression model was developed to correlate the process parameters with thermal efficiency (ηI), exergetic efficiency (ηII), vapor quality (x), and specific fuel consumption (SFC). A better determination coefficient (R2) was attained with the quadratic model, which showed 99.88%, 99.85%, 99.44%, and 99.80% for ηI, ηII, x, and SFC, respectively. Hence, numerical and graphical optimization was conducted operating the desirability function approach to get the suitable input variables to deliver the highest thermal and exergetic efficiencies with maximum vapor quality and minimal specific fuel consumption rate.